Growth, production and quality of pineapple in response to herbicide use - Leonardo Carvalho Brant Maia; Victor Martins Maia; Mário Henrique Melo e Lima; Ignacio Aspiazú; Rodinei Facco Pegoraro (Revista Brasileira de Fruticultura, 2012)
In pineapple fields, weed competition is exacerbated by the fact that the crop is small and has a very slow vegetative development. The objective of this study was to determine the effects of herbicides on growth, yield and quality of pineapple, cultivar 'Pérola'. The experimental design was in randomized blocks with four treatments and four replications. Treatments consisted of weeding by hoe and the herbicides diuron; fluazifop-p-butyl and atrazine + S-metolachlor applied in post-emergence. The characteristics evaluated monthly during the vegetative stage were stem diameter, D-leaf length, number of leaves, number of emitted leaves and percentage of natural floral induction. In the reproductive phase, evaluations were made of average fruit weight (g) with and without crown, fruits length and diameter, number of slip, slip-sucker and sucker type seedlings, determination of soluble solids and pH in the pulp. There was no effect of herbicide treatment on the vegetative growth characteristics. Stem diameter increased until 330 days after planting, showing a decrease after this period. The D-leaf grew over time in all treatments, although phytotoxicity symptoms were observed after the first application of herbicides. The traits evaluated on the reproductive phase showed no significant differences in response to treatments. Therefore, the use of diuron fluazifop-p-butyl and atrazine + S-metolachlor did not affect growth, yield and fruit quality of pineapple, cultivar 'Pérola'.